Artificial Intelligence-Aided Diagnosis Software to Identify Highly Suspicious Pulmonary Nodules - Lv, Jun; Li, Jianhui; Liu, Yanzhen; Zhang, Hong; Luo, Xiangfeng; Ren, Min; Gao, Yufan; Ma, Yanhe; Liang, Shuo; Yang, Yapeng; Song, Zhenchun; Gao, Guangming; et al. (Frontiers in Oncology, 2022)
Introduction: To evaluate the value of artificial intelligence (AI)-assisted software in the diagnosis of lung nodules using a combination of low-dose computed tomography (LDCT) and high-resolution computed tomography (HRCT). Method: A total of 113 patients with pulmonary nodules were screened using LDCT. For nodules with the largest diameters, an HRCT local-target scanning program (combined scanning scheme) and a conventional-dose CT scanning scheme were also performed. Lung nodules were subjectively assessed for image signs and compared by size and malignancy rate measured by AI-assisted software. The nodules were divided into improved visibility and identical visibility groups based on differences in the number of signs identified through the two schemes. Results: The nodule volume and malignancy probability for subsolid nodules significantly differed between the improved and identical visibility groups. For the combined scanning protocol, we observed significant between-group differences in subsolid nodule malignancy rates. Conclusion: Under the operation and decision of AI, the combined scanning scheme may be beneficial for screening high-risk populations.